2005
DOI: 10.1111/j.0022-2526.2005.01551.x
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Time Asymptotics for Periodic Solutions of the Modified Burgers Equation

Abstract: In this paper, we construct large-time asymptotic solution of the modified Burgers equation with sinusoidal initial conditions by using a balancing argument. These asymptotics are validated by a careful numerical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…(i) for t ≥ 100 a convergence of the numerical solution to the analytical one appears, (ii) for t ≥ 250 the MPC method has given results more accurate than the corresponding ones in [45], (iii) from t = 300 instead of t = 450 in [35] no visible differences in the curves of u and U (see Fig. 2) appear.…”
Section: Mbe3 Equationmentioning
confidence: 92%
See 2 more Smart Citations
“…(i) for t ≥ 100 a convergence of the numerical solution to the analytical one appears, (ii) for t ≥ 250 the MPC method has given results more accurate than the corresponding ones in [45], (iii) from t = 300 instead of t = 450 in [35] no visible differences in the curves of u and U (see Fig. 2) appear.…”
Section: Mbe3 Equationmentioning
confidence: 92%
“…The MBE equation, which has the strong nonlinear aspects of the governing equation ( is used in many practical transport problems such as those of nonlinear waves in a medium with low-frequency pumping or absorption, ion reflection at quasi-perpendicular shocks, turbulence transport, wave processes in thermoelastic media, transport and dispersion of pollutants in rivers and sediment transport, etc. Theoretical solutions of the MBE equation are found in, among other references, Harris [33], Sachdev and Rao [34], Sachdev et al [35], Inan and Ugurlu [36], while numerical solutions are found in Ramadan and El-Danaf [37] using the collocation method with quintic splines, Ramadan et al [38] with finite elements with a method based on the collocation of septic B-splines, Dağ et al [39] with finite elements with a method based on the collocation of cubic B-splines, Dağ et al [40] using both quadratic and cubic B-spline Galerkin finite-element methods, Saka and Dağ [41] with the use of a quartic B-spline collocation method, Saka and Dağ [42] with the use of a quintic B-spline collocation method, Irk [43] with the sextic B-spline collocation method, Temsah [44] using the El-Gendi method, Duan et al [45] using a lattice Boltzmann model, etc. The initial condition associated with Eq.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Example Consider MBE‐III equation (Equation with η = 3) with initial condition ux0=Asinπitalicxd,0<x<1, using d = π and A = 1 subject to boundary conditions: u0t=0,0tT, u1t=0,0tT. Sachdev et al constructed a solution to the above problem by means of asymptotic expansion and it can be represented as: uxt=ektf0xt+e4ktf1xt+e7ktf2xt+ where f0(),xt=A1sin()πxd,f1(),xt=B1tsin()2πitalicxd+B2sin()4πitalicxd,f2(),xt=g3()tsin()2πitalicxd+g4()tsin()3π<...>…”
Section: Numerical Experiments and Discussionmentioning
confidence: 99%
“…Periodic problem for the Hopf equation was studied in paper [15]. The asymptotic behavior for large time of solutions to the periodic problem for the generalized Burgers equations was studied in papers [18,23]. The existence of unique global solutions for the periodic problem to Korteweg-de Vries-Burgers equation was proved, and estimates of the large time decay rates of solutions were found in papers [2,16,22].…”
Section: Introductionmentioning
confidence: 99%